Changes in cross-border tourist traffic on the Poland–Belarus border, as exemplified by the Augustów Canal - Cyargeenka, Aliaksandr (Turyzm/Tourism, 2021)
The Augustów Canal is one of the unique tourist attractions of a Poland–Belarus borderland known for its highly valuable natural, cultural-historical and tourism-related features. From the beginning of the 21st century, following total renovation as well as the opening of both water and road versions of the Rudawka–Lesnaya border crossing (in 2005 and 2017 respectively), it has been possible to observe a many-fold increase in tourist traffic within the Augustów Canal tourist space. The present article thus helps fill a research gap with an up-to-date description of this intensification and an analysis of its dynamics in terms of the countries of origin of visiting tourists, its seasonality and choice of transport, be it by water (by boat) or by road (by bicycle or on foot). This study continues investigations into the influence of the easing of the border regime in Belarus (introduction of a visa-free zone) on the volume of tourist traffic. Factors influencing cross-border traffic on the Augustów Canal have been studied at local, regional, national and international levels (multi-scalar). Fieldwork has also been organised, using the participant-observer method, and statistical data from the Polish Border Guard has been analysed. Results confirm that the greatest use made of the Rudawka–Lesnaya crossing is by tourists from Poland and Belarus, with smaller numbers from Lithuania, Russia and Germany. Poles are the nation most often availing themselves of opportunities to cross the border by water, while Belarusians show a preference for the road crossing.